Readiness of higher education leaders to implement micro-credentials in Malaysia - Md Rami, Ahmad Aizuddin; Ismail, Ismi Arif; Sarman, Mohd Amin (International Journal of Evaluation and Research in Education (IJERE), 2024)
In Malaysia, higher education institutions (HEIs) have made significant efforts to integrate micro-credentials into their educational systems. However, the status of micro-credentials among these institutions remains ambiguous. Furthermore, there is a few research on university leaders in Malaysia. As a result, a study was conducted to investigate the preparedness of university leaders in implementing micro-credentials within HEIs. This research aimed to unveil the interconnected relationship among key stakeholders and emphasize the necessity for university leaders to reevaluate their roles and perspectives within their respective institutions. The current study used a qualitative approach via a case study method involving five informants from university leaders in public HEIs in Peninsular Malaysia. For data collection and analysis, this study used focus group discussion and thematic analysis respectively. The data analysis led to the development of the major themes that emerged from findings: i) the conceptualization of micro-credentials; ii) human capitals; iii) infrastructures; iv) accreditation; and v) accountability, all of which are referred to as challenges faced by university leaders. The current study hopes that the top university leaders are able to demonstrate clear vision and unwavering commitment that can contribute to the successful integration of micro-credentials within the HEI landscape.